2021
DOI: 10.1007/s10792-021-01819-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the partial blink rate and ocular surface parameters

Abstract: Purpose To elucidate the relationship between partial blink rate (PBR) and ocular surface parameters. Methods We conducted a retrospective cross-sectional study of the patients who visited the Kim's Eye Hospital between March 2020 and July 2020. Blinking dynamics, tear film lipid layer thickness (LLT), noninvasive tear film break-up time (NITBUT), tear meniscus height (TMH), and meibomian gland (MG) dropout rate were assessed using the IDRA Ò Ocular surface analyzer (SBM SISTEMI, Inc., Torino, Italy) (IDRA). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…Previous studies have shown that blinking is associated with DED, psychological status, and systemic diseases (58). PB was more prevalent in patients with DED than non-DED, and PB was correlated with DED in our study (57). However, no significant correlation was found between PBR and anxiety and depression scores in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have shown that blinking is associated with DED, psychological status, and systemic diseases (58). PB was more prevalent in patients with DED than non-DED, and PB was correlated with DED in our study (57). However, no significant correlation was found between PBR and anxiety and depression scores in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…Blinking serves a vital function in preserving moisture, the unity of the ocular surface of the lipid layer, and the extension of tear lipids. Increasing the PBR leads to inadequate lipid distribution, which may increase tear evaporation ( 56 , 57 ). Previous studies have shown that blinking is associated with DED, psychological status, and systemic diseases ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blink can maintain tear film stability of the ocular surface by promoting the reconstruction and development of the lipid layer ( 53 , 54 ). can be covered by tears through complete blinking, preventing damage from DED.…”
Section: Discussionmentioning
confidence: 99%
“…The easier secretion of a clearer meibum after IPL–MGX therapy significantly thickened LLT and statistically increased TMH. However, final mean LLT (53.99 nm, Figure 1 ) was not thick enough to cover the whole cornea according to the international grade scale of interferometer IDRA test that LLT beyond 80 nm may appear as a stable and thick lipid layer containing colorful oil [ 27 , 28 ], leading to longer NIBUT. Even total mean lissamine green scores in our study were lower, indicating improvement of ocular surface conditions after first IPL–MGX combined therapy compared to pretreatment values, but the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%